DESAIN SIGN SYSTEM SEBAGAI MEDIA INFORMASI DI LINGKUNGAN LPI DARUSSALAM SURABAYA - Masnuna (Jurnal Bahasa Rupa, 2023)
The Darussalam Islamic Education Institute has study groups for KB, PPT, Kindergarten, and TPA. The building environment has not been equipped with a conducive environment, with the large number of study groups and the number of students making students feel less comfortable and safe. Even though every corner at LPI Darussalam can be used as a vehicle for learning to develop the basic abilities of growing children. LPI Darussalam requires a sign system as an information medium for spatial directions, space markers, and appeals to support the student learning process by using the pre-production stage including design strategies, communication strategies, creative strategies, and media strategies, the production stage includes visual concepts, and the post-production stage includes media implementation. Thus the sign system can be used as learning and child development in the aspects of language, art, motorism, and cognitive, so that students feel safe and comfortable when studying at school.